Injection-molded ultrahigh-strength titanium alloy and preparation method thereof
Through the powder pressure-free vacuum sintering and solid solution-aging heat treatment process, the Ti-Al-V-Cr-Mo-Fe system ultra-high strength titanium alloy was prepared, which solved the problem that traditional processes were difficult to produce complex shape ultra-high strength titanium alloys, and realized the problem of High strength and good mechanical properties.
Patent Information
- Application Number
- CN202411619845.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-02-18
AI Technical Summary
The prior art is difficult to produce ultra-high strength titanium alloys in complex shapes efficiently and at low cost, and traditional melting and casting processes are difficult to meet the needs of modern high-tech equipment.
通过粉末无压真空烧结工艺制备Ti-Al-V-Cr-Mo-Fe系超高强钛合金,并采用固溶-时效热处理工艺调控合金的微观组织,提高其综合力学性能。
Ultra-high strength titanium alloys with density above 99.0%, room temperature tensile strength exceeding 1300MPa, yield strength exceeding 1200MPa, and elongation exceeding 8.0%, meeting the material needs of modern high-tech equipment.
Smart Images

Figure CN119464834A_ABST
Abstract
Description
[Technical field]
[0001] The invention relates to the technical field of powder metallurgy materials, and in particular to an injection-molded ultra-high-strength titanium alloy and a preparation method thereof. [Background technology]
[0002] Titanium and titanium alloys are widely used in consumer electronics, aerospace, medical equipment, high-end manufacturing and other fields due to their low density, high strength, excellent corrosion resistance and good biocompatibility. However, with the continuous development of the high-tech field, higher and higher requirements are placed on materials including titanium alloys. The strength of the most widely used TC4 titanium alloy (room temperature tensile strength is less than 1100MPa) can no longer meet the requirements of high performance, and the design requirements of complex structures of titanium alloys can no longer meet the needs of high-tech equipment. Ultra-high-strength titanium alloys with room temperature tensile strength exceeding 1300MPa can achieve lightweight and miniaturization, and have become the preferred material in the high-tech field. However, due to the poor machinability of titanium alloys, traditional machining processes are difficult to efficiently and low-cost produce complex-shaped titanium alloy products.
[0003] Powder injection molding technology has short process, high energy efficiency and good forming flexibility, and can realize the economic production of complex-shaped parts. However, the current ultra-high-strength titanium alloy composition and process are designed for traditional melting and casting processes, and the powder vacuum pressureless sintering and injection molding processes have not yet produced ultra-high-strength titanium alloys. Therefore, it is necessary to design ultra-high-strength titanium alloy compositions for the powder pressureless sintering process, and develop corresponding sintering and heat treatment process systems to realize the injection molding process to prepare complex-shaped ultra-high-strength titanium alloys, thereby meeting the needs of modern high-tech equipment.
[0004] Therefore, it is necessary to study an injection molded ultra-high strength titanium alloy and a preparation method thereof to address the deficiencies of the prior art and to solve or alleviate one or more of the above problems. [Summary of the invention]
[0005] In view of this, the present invention provides an injection-molded ultra-high strength titanium alloy and a preparation method thereof, which regulates the microstructure of the alloy through a heat treatment process after sintering, and improves its comprehensive mechanical properties through dispersion strengthening, precipitation strengthening, and the like.
[0006] On the one hand, the present invention provides an injection-molded ultra-high strength titanium alloy, which is a Ti-Al-V-Cr-Mo-Fe series ultra-high strength titanium alloy, and the mass percentage of each element is as follows: Al: 5.3-5.6, V: 3.4-4.0, Cr: 0.2-0.8, Mo: 4.2-5.2, Fe: 3.6-4.6, and the balance is Ti.
[0007] According to the above aspects and any possible implementation, an implementation is further provided, wherein the powder particle size of the injection molded ultra-high strength titanium alloy is 0 to 30 μm.
[0008] According to the aspects and any possible implementations described above, an implementation is further provided, wherein the oxygen content of the powder of the injection molded ultra-high strength titanium alloy is less than 2300 ppm.
[0009] According to the aspects and any possible implementations described above, an implementation is further provided, wherein the density of the injection-molded ultra-high strength titanium alloy is greater than 99.0%, the room temperature tensile strength is greater than 1300 MPa, the yield strength is greater than 1200 MPa, and the elongation is greater than 8.0%.
[0010] According to the above aspects and any possible implementation, a method for preparing an injection molded ultra-high strength titanium alloy is further provided, which is used to prepare the injection molded ultra-high strength titanium alloy, and the preparation method comprises the following steps:
[0011] Step 1, preparing titanium alloy powder raw material according to a preset ratio and composition;
[0012] Step 2: premixing the titanium alloy powder raw material with a binder corresponding to a corresponding loading amount in a mixer to obtain a mixture;
[0013] Step 3, putting the mixed material into a kneading machine and kneading to obtain feed material;
[0014] Step 4, crushing and granulating the kneaded feed to obtain pellets;
[0015] Step 5, putting the pellets into an injection machine and injecting them to obtain injection material;
[0016] Step six, degreasing the injection material to obtain a degreased material;
[0017] Step seven, sintering the degreased material to obtain a sintered material;
[0018] Step eight, heat treating the sintered material to obtain an injection molded ultra-high strength titanium alloy;
[0019] Step nine: Test and characterize the injection molded ultra-high strength titanium alloy.
[0020] According to the above aspects and any possible implementation, an implementation is further provided, wherein the titanium alloy powder raw material in step one has a D50 particle size of 7 to 15 μm and an oxygen content of less than 2280 ppm.
[0021] According to the above aspects and any possible implementation, an implementation is further provided, wherein the binder in the mixture in step 2 is a wax-based binder including paraffin and / or a plastic-based binder including polyoxymethylene, and the titanium alloy powder raw material accounts for 56% to 70% of the total volume of the mixture,
[0022] In step 3, the kneading temperature of the plastic-based binder system is 180-190°C, and the kneading time is 1-3h; the kneading temperature of the wax-based system is 155-165°C, and the kneading time is 1-3h;
[0023] In step 4, the granulation temperature of the plastic-based binder system is 180°C, the granulation temperature of the wax-based binder system is 160°C, the extrusion speed is 10-20Hz, the feeding speed is 5-10Hz, the cutting speed is 5-10Hz, the particle size of the pellets is 3mm, and the particle length is 2-4mm.
[0024] According to the aspects and any possible implementation methods described above, an implementation method is further provided, wherein the injection mold in step five is a stretch strip mold, and the injection parameters used for plastic-based feeding are injection temperature of 180-190°C, injection pressure of 180-195 bar, injection speed of 60-80%, and mold temperature of 50-65°C; the injection parameters used for wax-based feeding are 155-170°C, injection pressure of 180-195 bar, injection speed of 60-80%, and mold temperature of 40-60°C.
[0025] According to the aspects and any possible implementation methods described above, an implementation method is further provided, in step six, the degreasing method of the plastic-based stretched strip injection blank is oxalic acid degreasing, and its parameters are: degreasing temperature 120-150°C, and degreasing time is 8-18 hours; the degreasing method of the wax-based stretched strip injection blank is solvent degreasing, the solvent used is trichloroethylene, and the solvent degreasing parameters are: solvent temperature 30-60°C, and degreasing time is 8-20 hours.
[0026] According to the above aspects and any possible implementation, an implementation is further provided, in step seven, sintering is carried out in a molybdenum sheet vacuum sintering furnace, the temperature is increased at a rate of 2 to 5°C / min, and thermal debinding is performed at 300°C, 450°C, and 550°C for 1 to 2 hours, respectively, and then the temperature is increased to 1000 to 1300°C at a rate of 2 to 10°C / min and the temperature is maintained for 1 to 5 hours, and the furnace is cooled to room temperature; the thermal debinding atmosphere is high-purity argon gas, and the vacuum degree during vacuum pressureless sintering is 0.01Pa;
[0027] In step eight, the heat treatment is a solution-aging heat treatment, the solution temperature is 800-1000°C, the heating rate is 5-15°C / min, the temperature is kept for 1-8h, and then the aging treatment is carried out after rapid cooling to room temperature; the aging temperature is 400-700°C, the heating rate is 5-15°C / min, the temperature is kept for 1-6h, and the temperature is rapidly cooled to room temperature.
[0028] Compared with the prior art, the present invention can achieve the following technical effects:
[0029] 1. The injection molded ultra-high strength titanium alloy prepared by heat treatment after pressureless vacuum sintering of powder in the present invention has a density of >99.0%, a room temperature tensile strength of >1300MPa, a yield strength of >1200MPa, and an elongation of >8.0%, and has very excellent comprehensive mechanical properties;
[0030] 2. The present invention significantly enhances the strength of titanium alloys through the synergistic effect of multiple strengthening mechanisms such as solid solution strengthening and precipitation strengthening, and obtains ultra-high-strength titanium alloys through vacuum pressureless sintering of powders without the assistance of pressure or hot working.
[0031] Of course, any product implementing the present invention does not necessarily need to achieve all of the above-mentioned technical effects at the same time.
Brief Description of the Drawings
[0032] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0033] Figure 1 is a microscopic photo of the metallographic structure of the sintered sample of Example 1 of the present invention;
[0034] Figure 2 This is a microscopic photograph of the metallographic structure of the heat-treated sample in Example 1 of the present invention. [Specific implementation method]
[0035] In order to better understand the technical solution of the present invention, the embodiments of the present invention are described in detail below with reference to the accompanying drawings.
[0036] It should be clear that the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] The terms used in the embodiments of the present invention are only for the purpose of describing specific embodiments, and are not intended to limit the present invention. The singular forms "a", "said" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0038] The invention provides an injection-molded ultra-high-strength titanium alloy. The injection-molded ultra-high-strength titanium alloy is a Ti-Al-V-Cr-Mo-Fe series ultra-high-strength titanium alloy, and the mass percentage of each element is as follows: Al: 5.3-5.6, V: 3.4-4.0, Cr: 0.2-0.8, Mo: 4.2-5.2, Fe: 3.6-4.6, and the balance is Ti.
[0039] In a specific embodiment, the powder particle size of the injection molded ultra-high strength titanium alloy is 0 to 30 μm.
[0040] In a specific embodiment, the oxygen content of the powder of the injection molded ultra-high strength titanium alloy is less than 2300 ppm.
[0041] In a specific embodiment, the density of the injection-molded ultra-high strength titanium alloy is greater than 99.0%, the room temperature tensile strength is greater than 1300 MPa, the yield strength is greater than 1200 MPa, and the elongation is greater than 8.0%.
[0042] The present invention also provides a method for preparing an injection-molded ultra-high-strength titanium alloy, which is used to prepare the injection-molded ultra-high-strength titanium alloy. The preparation method comprises the following steps:
[0043] Step 1, preparing titanium alloy powder raw material according to a preset ratio and composition;
[0044] Step 2: premixing the titanium alloy powder raw material with a binder corresponding to a corresponding loading amount in a mixer to obtain a mixture;
[0045] Step 3, putting the mixed material into a kneading machine and kneading to obtain feed material;
[0046] Step 4, crushing and granulating the kneaded feed to obtain pellets;
[0047] Step 5, putting the pellets into an injection machine and injecting them to obtain injection material;
[0048] Step six, degreasing the injection material to obtain a degreased material;
[0049] Step seven, sintering the degreased material to obtain a sintered material;
[0050] Step eight, heat treating the sintered material to obtain an injection molded ultra-high strength titanium alloy;
[0051] Step nine: Test and characterize the injection molded ultra-high strength titanium alloy.
[0052] In a specific embodiment, the titanium alloy powder raw material in step 1 has a D50 particle size of 7 to 15 μm and an oxygen content of less than 2280 ppm.
[0053] In a specific embodiment, the binder in the mixture in step 2 is a wax-based binder including paraffin and / or a plastic-based binder including polyoxymethylene, and the titanium alloy powder raw material accounts for 56% to 70% of the total volume of the mixture.
[0054] In step 3, the kneading temperature of the plastic-based binder system is 180-190°C, and the kneading time is 1-3h; the kneading temperature of the wax-based system is 155-165°C, and the kneading time is 1-3h;
[0055] In step 4, the granulation temperature of the plastic-based binder system is 180°C, the granulation temperature of the wax-based binder system is 160°C, the extrusion speed is 10-20Hz, the feeding speed is 5-10Hz, the cutting speed is 5-10Hz, the particle size of the pellets is 3mm, and the particle length is 2-4mm.
[0056] In a specific embodiment, the injection mold in step five is a stretch strip mold, and the injection parameters used for plastic-based feeding are injection temperature of 180-190°C, injection pressure of 180-195 bar, injection speed of 60-80%, and mold temperature of 50-65°C; the injection parameters used for wax-based feeding are 155-170°C, injection pressure of 180-195 bar, injection speed of 60-80%, and mold temperature of 40-60°C.
[0057] In a specific embodiment, the degreasing method of the plastic-based tensile strip injection blank in step six is oxalic acid degreasing, and its parameters are: degreasing temperature 120-150°C, and degreasing time 8-18 hours; the degreasing method of the wax-based tensile strip injection blank is solvent degreasing, the solvent used is trichloroethylene, and the solvent degreasing parameters are: solvent temperature 30-60°C, and degreasing time 8-20 hours.
[0058] In a specific embodiment, the sintering in step seven is carried out in a molybdenum sheet vacuum sintering furnace, the temperature is increased at a rate of 2 to 5 ° C / min, and the temperature is kept at 300 ° C, 450 ° C, and 550 ° C for 1 to 2 hours for thermal degreasing, and then the temperature is increased to 1000 to 1300 ° C at a rate of 2 to 10 ° C / min and kept for 1 to 5 hours, and the furnace is cooled to room temperature; the hot degreasing atmosphere is high-purity argon, and the vacuum degree during vacuum pressureless sintering is 0.01 Pa;
[0059] In step eight, the heat treatment is a solid solution-aging heat treatment, the solid solution temperature is 800-1000°C, the heating rate is 5-15°C / min, the temperature is kept for 1-8 hours, and then the aging treatment is carried out after rapid cooling to room temperature; the aging temperature is 400-700°C, the heating rate is 5-15°C / min, the temperature is kept for 1-6 hours, and the temperature is rapidly cooled to room temperature. The synergistic effect of various strengthening mechanisms such as solid solution strengthening and precipitation strengthening significantly enhances the strength of titanium alloys, and ultra-high strength titanium alloys are obtained by vacuum pressureless sintering of powders without the assistance of pressure or hot working.
[0060] Example 1
[0061] The preparation method of this embodiment comprises the following steps:
[0062] Step 1, raw material preparation: prepare 2 kg of Ti-5.4Al-3.6V-0.5Cr-4.6Mo-3.8Fe titanium alloy powder, the D50 particle size of the powder is 10.2 μm, and the oxygen content is 2000 ppm. Use a plastic-based binder.
[0063] Step 2: Premixing: Premix the metal powder with the plastic-based binder corresponding to 64% loading in a V-type mixer for 0.5 h.
[0064] Step 3, preparing feed material: putting the powder mixed in step 2 and the binder into an SH-2 atmosphere kneader to knead to obtain feed material at a kneading temperature of 180° C. and a kneading time of 2 h.
[0065] Step 4, granulation: crush and granulate the kneaded feed. The granulation equipment is a CF-φ60 double-arm extruder granulator. The specific parameters are: granulation temperature is 180°C, extrusion speed is 10Hz, feeding speed is 5Hz, cutting speed is 5Hz, particle size is 3mm, and particle length is 3mm.
[0066] Step 5, injection molding: put the feed obtained by granulation in step 4 into JPH80E Hongli 80-ton injection machine for injection, and the injection mold is a stretch bar mold. The injection parameters are as follows: injection temperature is 180°C, injection pressure is 180 bar, injection speed is 60%, and mold temperature is 60°C.
[0067] Step 6, degreasing: put the sample obtained in step 5 into the oxalic acid degreasing furnace for degreasing. The degreasing parameters are: rinsing temperature 75℃, heat preservation for 30min; first stage degreasing temperature 110℃, heat preservation for 60min; second stage degreasing temperature 125℃, heat preservation for 530min; third stage degreasing temperature 135℃, heat preservation for 25min. Oxalic acid degreasing obtains the acid-degreasing body.
[0068] Step 7, sintering: put the debinded blank in step 6 into the BFZS1903111 molybdenum sheet high vacuum sintering furnace for debinding and sintering. The thermal debinding is heated at a heating rate of 5°C / min, and kept at three different temperature sections of 300°C, 450°C, and 550°C for 1h respectively. The thermal debinding atmosphere is high-purity argon. After thermal debinding, the temperature is raised to 1300°C at a rate of 10°C / min, the holding time is 2h, and the sintering vacuum is 0.01Pa.
[0069] Step 8, heat treatment: The sample obtained by sintering in step 7 was subjected to solution-aging heat treatment. The solution temperature was 900°C, the heating rate was 10°C / min, the temperature was kept for 4 hours, and then the aging treatment was carried out after rapid cooling to room temperature; the aging temperature was 500°C, the heating rate was 10°C / min, the temperature was kept for 4 hours, and the temperature was rapidly cooled to room temperature.
[0070] Step 9: Perform density test on the heat-treated sample prepared in step 8. The test method is implemented in accordance with the national implementation standard GB / T1423-1996. The density of the sample after heat treatment is 99.6%.
[0071] Step 10: Test the room temperature tensile mechanical properties of the heat-treated sample prepared in step 8. The test method is implemented in accordance with the national standard GB / T228.1-2010. The tensile strength of the heat-treated sample is 1343 MPa, the yield strength is 1232 MPa, and the elongation is 10.8%.
[0072] Step 11: metallographic sample preparation and characterization of the sintered sample prepared in step 7 and the heat-treated sample prepared in step 8. Grind the sample with sandpaper of different meshes, then polish it, and use Kroll reagent (HF: H2SO4 (concentrated): H2O volume ratio of 1:3:15-30) to erode the sample surface for 60 seconds. After the corrosion is completed, put it in an alcohol solution and ultrasonically clean it for 1 minute. After taking it out, blow dry the alcohol on the sample surface to obtain a metallographic sample.
[0073] Step 12: characterize the metallographic samples prepared in step 11 using a SU8100 cold field emission scanning electron microscope. Figure 1 is a microscopic photo of the metallographic structure of the sintered sample of Example 1 of the present invention; Figure 2 This is a microscopic photograph of the metallographic structure of the heat-treated sample in Example 1 of the present invention.
[0074] Example 2
[0075] The preparation method of this embodiment comprises the following steps:
[0076] Step 1, raw material preparation: prepare 2 kg of Ti-5.5Al-3.5V-0.6Cr-4.8Mo-3.9Fe titanium alloy powder, the D50 particle size of the powder is 11.8 μm, and the oxygen content is 2200 ppm.
[0077] Step 2: Premixing: Premix the metal powder with the plastic-based binder corresponding to 64% loading in a V-type mixer for 0.5 h.
[0078] Step 3, preparing feed material: putting the powder mixed in step 2 and the binder into an SH-2 atmosphere kneader to knead to obtain feed material at a kneading temperature of 185° C. and a kneading time of 2 h.
[0079] Step 4, granulation: crush and granulate the kneaded feed. The granulation equipment is a CF-φ60 double-arm extruder granulator. The specific parameters are: granulation temperature is 180°C, extrusion speed is 10Hz, feeding speed is 5Hz, cutting speed is 5Hz, particle size is 3mm, and particle length is 3mm.
[0080] Step 5, injection molding: put the feed obtained by granulation in step 4 into JPH80E Hongli 80-ton injection machine for injection, and the injection mold is a stretch bar mold. The injection parameters are as follows: injection temperature is 185°C, injection pressure is 185 bar, injection speed is 75%, and mold temperature is 60°C.
[0081] Step 6, degreasing: put the sample obtained in step 5 into the oxalic acid degreasing furnace for degreasing. The degreasing parameters are: rinsing temperature 70℃, heat preservation for 30min; first stage degreasing temperature 120℃, heat preservation for 60min; second stage degreasing temperature 130℃, heat preservation for 525min; third stage degreasing temperature 130℃, heat preservation for 30min. Oxalic acid degreasing obtains the acid-degreasing body.
[0082] Step 7, sintering: put the debinded blank in step 6 into the BFZS1903111 molybdenum sheet high vacuum sintering furnace for debinding and sintering. The thermal debinding is heated at a heating rate of 5°C / min, and kept at three different temperature sections of 300°C, 450°C, and 550°C for 1h respectively. The thermal debinding atmosphere is high-purity argon. After thermal debinding, the temperature is raised to 1300°C at a rate of 10°C / min, the holding time is 2h, and the sintering vacuum is 0.01Pa.
[0083] Step 8, heat treatment: The sample sintered in step 7 was subjected to solution-aging heat treatment. The solution temperature was 800°C, the heating rate was 10°C / min, the temperature was kept for 4 hours, and then the aging treatment was carried out after rapid cooling to room temperature; the aging temperature was 400°C, the heating rate was 10°C / min, the temperature was kept for 4 hours, and the temperature was rapidly cooled to room temperature.
[0084] Step 9: Perform density test on the heat-treated sample prepared in step 8. The test method is implemented in accordance with the national implementation standard GB / T1423-1996. The density of the sample after heat treatment is 99.4%.
[0085] Step 10: Test the room temperature tensile mechanical properties of the heat-treated sample prepared in step 8. The test method is implemented in accordance with the national standard GB / T228.1-2010. The tensile strength of the heat-treated sample is 1324 MPa, the yield strength is 1215 MPa, and the elongation is 9.8%.
[0086] Step 11: metallographic sample preparation and characterization of the heat-treated sample prepared in step 8. Grind the sample with sandpaper of different meshes, then polish it, and use Kroll reagent (HF: H2SO4 (concentrated): H2O volume ratio of 1:3:15-30) to erode the sample surface for 60 seconds. After the corrosion is completed, put it in an alcohol solution and ultrasonically clean it for 1 minute. After taking it out, blow dry the alcohol on the sample surface to obtain a metallographic sample.
[0087] Step 12: characterize the metallographic sample prepared in step 11 using a SU8100 cold field emission scanning electron microscope.
[0088] Example 3
[0089] The preparation method of this embodiment comprises the following steps:
[0090] Step 1, raw material preparation: prepare 2 kg of Ti-5.6Al-3.8V-0.7Cr-4.8Mo-3.9Fe titanium alloy powder, the D50 particle size of the powder is 10.2 μm, and the oxygen content is 2000 ppm.
[0091] Step 2: premixing: premix the metal powder with the wax-based binder corresponding to 64% loading in a V-type mixer for 0.5 h.
[0092] Step 3, preparing feed material: putting the powder mixed in step 2 and the binder into an SH-2 atmosphere kneader to knead to obtain feed material at a kneading temperature of 160° C. and a kneading time of 2 h.
[0093] Step 4, granulation: crush and granulate the kneaded feed. The granulation equipment is a CF-φ60 double-arm extruder granulator. The specific parameters are: granulation temperature is 160°C, extrusion speed is 10Hz, feeding speed is 5Hz, cutting speed is 5Hz, particle size is 3mm, and particle length is 3mm.
[0094] Step 5, injection molding: put the feed obtained by granulation in step 4 into JPH80E Hongli 80-ton injection machine for injection, and the injection mold is a stretch bar mold. The injection parameters are as follows: injection temperature is 160°C, injection pressure is 170 bar, injection speed is 65%, and mold temperature is 40°C.
[0095] Step 6, degreasing: the sample obtained in step 5 is placed in a trichloroethylene solution for degreasing. The degreasing parameters are: degreasing temperature: 60°C, degreasing time: 20 hours. Solvent degreasing obtains a degreased body.
[0096] Step 7, sintering: put the debinded blank in step 6 into the BFZS1903111 molybdenum sheet high vacuum sintering furnace for debinding and sintering. The thermal debinding is heated at a heating rate of 5°C / min, and kept at three different temperature sections of 300°C, 450°C, and 550°C for 1h respectively. The thermal debinding atmosphere is high-purity argon. After thermal debinding, the temperature is raised to 1300°C at a rate of 10°C / min, the holding time is 2h, and the sintering vacuum is 0.01Pa.
[0097] Step 8, heat treatment: The sample obtained by sintering in step 7 was subjected to solution-aging heat treatment. The solution temperature was 900°C, the heating rate was 10°C / min, and the temperature was kept for 2 hours, followed by rapid cooling to room temperature and then aging treatment; the aging temperature was 500°C, the heating rate was 10°C / min, and the temperature was kept for 2 hours, followed by rapid cooling to room temperature.
[0098] Step 9: Perform density test on the heat-treated sample prepared in step 8. The test method is implemented in accordance with the national implementation standard GB / T1423-1996. The density of the sample after heat treatment is 99.5%.
[0099] Step 10: Test the room temperature tensile mechanical properties of the heat-treated sample prepared in step 8. The test method is implemented in accordance with the national standard GB / T228.1-2010. The tensile strength of the heat-treated sample is 1337 MPa, the yield strength is 1230 MPa, and the elongation is 8.1%.
[0100] Step 11: metallographic sample preparation and characterization of the heat-treated sample prepared in step 8. Grind the sample with sandpaper of different meshes, then polish it, and use Kroll reagent (HF: H2SO4 (concentrated): H2O volume ratio of 1:3:15-30) to erode the sample surface for 60 seconds. After the corrosion is completed, put it in an alcohol solution and ultrasonically clean it for 1 minute. After taking it out, blow dry the alcohol on the sample surface to obtain a metallographic sample.
[0101] Step 12: characterize the metallographic sample prepared in step 11 using a SU8100 cold field emission scanning electron microscope.
[0102] Example 4
[0103] The preparation method of this embodiment comprises the following steps:
[0104] Step 1, raw material preparation: prepare 2 kg of Ti-5.4Al-3.8V-0.7Cr-4.8Mo-4.2Fe titanium alloy powder, the D50 particle size of the powder is 11.8 μm, and the oxygen content is 2200 ppm.
[0105] Step 2: premixing: premix the metal powder with the wax-based binder corresponding to 64% loading in a V-type mixer for 0.5 h.
[0106] Step 3, preparing feed material: putting the powder mixed in step 2 and the binder into an SH-2 atmosphere kneader to knead to obtain feed material at a kneading temperature of 165° C. and a kneading time of 2 h.
[0107] Step 4, granulation: crush and granulate the kneaded feed. The granulation equipment is a CF-φ60 double-arm extruder granulator. The specific parameters are: granulation temperature is 160°C, extrusion speed is 10Hz, feeding speed is 5Hz, cutting speed is 5Hz, particle size is 3mm, and particle length is 3mm.
[0108] Step 5, injection molding: put the feed obtained by granulation in step 4 into JPH80E Hongli 80-ton injection machine for injection, and the injection mold is a stretch bar mold. The injection parameters are as follows: injection temperature is 165°C, injection pressure is 180 bar, injection speed is 70%, and mold temperature is 40°C.
[0109] Step 6, degreasing: the sample obtained in step 5 is placed in a trichloroethylene solution for degreasing. The degreasing parameters are: degreasing temperature: 55°C, degreasing time: 18h. Solvent degreasing obtains a degreased body.
[0110] Step 7, sintering: put the debinded blank in step 6 into the BFZS1903111 molybdenum sheet high vacuum sintering furnace for debinding and sintering. During thermal debinding, the temperature is increased at a rate of 5°C / min, and the temperature is kept at 300°C, 450°C, and 550°C for 1h respectively. The thermal debinding atmosphere is high-purity argon. After thermal debinding, the temperature is increased at a rate of 10°C / min to a sintering temperature of 1300°C, the holding time is 2h, and the sintering vacuum is 0.01Pa.
[0111] Step 8, heat treatment: The sample obtained by sintering in step 7 was subjected to solution-aging heat treatment. The solution temperature was 800°C, the heating rate was 10°C / min, the temperature was kept for 6 hours, and then the aging treatment was carried out after rapid cooling to room temperature; the aging temperature was 400°C, the heating rate was 10°C / min, the temperature was kept for 6 hours, and the temperature was rapidly cooled to room temperature.
[0112] Step 9: Perform density test on the heat-treated sample prepared in step 8. The test method is implemented in accordance with the national implementation standard GB / T1423-1996. The density of the sample after heat treatment is 99.3%.
[0113] Step 10: Test the room temperature tensile mechanical properties of the heat-treated sample prepared in step 8. The test method is implemented in accordance with the national standard GB / T228.1-2010. The tensile strength of the heat-treated sample is 1337 MPa, the yield strength is 1228 MPa, and the elongation is 9.2%.
[0114] Step 11: metallographic sample preparation and characterization of the heat-treated sample prepared in step 8. Grind the sample with sandpaper of different meshes, then polish it, and use Kroll reagent (HF: H2SO4 (concentrated): H2O volume ratio of 1:3:15-30) to erode the sample surface for 60 seconds. After the corrosion is completed, put it in an alcohol solution and ultrasonically clean it for 1 minute. After taking it out, blow dry the alcohol on the sample surface to obtain a metallographic sample.
[0115] Step 12: characterize the metallographic sample prepared in step 11 using a SU8100 cold field emission scanning electron microscope.
[0116] The invention provides an injection-molded ultra-high-strength titanium alloy and a preparation method thereof. The high-strength titanium alloy is a Ti-Al-V-Cr-Mo-Fe series ultra-high-strength titanium alloy, and the mass percentage of each element is as follows: Al: 5.3-5.6, V: 3.4-4.0, Cr: 0.2-0.8, Mo: 4.2-5.2, Fe: 3.6-4.6, and the balance is Ti. First, the titanium alloy powder is pre-mixed with a binder. Then, the feed is kneaded in a kneader to obtain a feed, and the feed is crushed and granulated for injection molding to obtain an injection blank sample. Subsequently, the injection blank is degreased and sintered to obtain a sintered sample. Finally, heat treatment is performed to strengthen the sample. The tensile properties of the heat-treated sample are tested at room temperature, and the results show that the room temperature tensile strength is greater than 1300MPa, the yield strength is greater than 1200MPa, and the elongation is greater than 8.0%. The invention regulates the microstructure of the alloy through a heat treatment process after sintering, and improves its comprehensive mechanical properties through dispersion strengthening, precipitation strengthening, and the like.
[0117] The above is a detailed introduction to an injection molded ultra-high strength titanium alloy and its preparation method provided in the embodiment of the present application. The description of the above embodiment is only used to help understand the method and its core idea of the present application; at the same time, for those skilled in the art, according to the idea of the present application, there will be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.
[0118] For example, certain words are used in the specification and claims to refer to specific components. Those skilled in the art should understand that hardware manufacturers may use different nouns to refer to the same component. This specification and claims do not use differences in names as a way to distinguish components, but use differences in the functions of components as the criteria for distinction. As mentioned throughout the specification and claims, "including" and "comprising" are open-ended terms, so they should be interpreted as "including / including but not limited to". "Approximately" means that within an acceptable error range, those skilled in the art can solve the technical problem within a certain error range and basically achieve the technical effect. The subsequent description of the specification is a preferred embodiment of the present application, but the description is for the purpose of illustrating the general principles of the present application, and is not used to limit the scope of the present application. The scope of protection of the present application shall be determined by the definition of the attached claims.
[0119] It should also be noted that the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a product or system including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such a product or system. In the absence of more restrictions, the elements defined by the sentence "comprises a ..." do not exclude the existence of other identical elements in the product or system including the elements.
[0120] It should be understood that the term "and / or" used in this article is only a description of the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0121] The above description shows and describes several preferred embodiments of the present application, but as mentioned above, it should be understood that the present application is not limited to the form disclosed herein, and should not be regarded as excluding other embodiments, but can be used in various other combinations, modifications and environments, and can be modified within the scope of the application concept described herein through the above teachings or the technology or knowledge of the relevant field. The changes and modifications made by those skilled in the art do not deviate from the spirit and scope of the present application, and should be within the scope of protection of the claims attached to the present application.
Claims
1. An injection molded ultra-high strength titanium alloy, characterized in that: The injection molded ultra-high strength titanium alloy is a Ti-Al-V-Cr-Mo-Fe series ultra-high strength titanium alloy, and the mass percentage of each element is as follows: Al: 5.3-5.6, V: 3.4-4.0, Cr: 0.2-0.8, Mo: 4.2-5.2, Fe: 3.6-4.6, and the balance is Ti.
2. The injection molded ultra-high strength titanium alloy according to claim 1, characterized in that: The particle size of the powder of the injection-molded ultra-high-strength titanium alloy is 0 to 30 μm.
3. The injection molded ultra-high strength titanium alloy according to claim 1, characterized in that: The powder oxygen content of the injection-molded ultra-high-strength titanium alloy is less than 2300 ppm.
4. The injection molded ultra-high strength titanium alloy according to claim 1, characterized in that: The injection-molded ultra-high-strength titanium alloy has a density greater than 99.0%, a room temperature tensile strength greater than 1300 MPa, a yield strength greater than 1200 MPa, and an elongation greater than 8.0%.
5. A method for preparing an injection molded ultra-high strength titanium alloy, used for preparing the injection molded ultra-high strength titanium alloy according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: Step 1, preparing titanium alloy powder raw material according to a preset ratio and composition; Step 2: premixing the titanium alloy powder raw material with a binder corresponding to a corresponding loading amount in a mixer to obtain a mixture; Step 3, putting the mixed material into a kneading machine and kneading to obtain feed material; Step 4, crushing and granulating the kneaded feed to obtain pellets; Step 5, putting the pellets into an injection machine and injecting them to obtain injection material; Step six, degreasing the injection material to obtain a degreased material; Step seven, sintering the degreased material to obtain a sintered material; Step eight, heat treating the sintered material to obtain an injection molded ultra-high strength titanium alloy; Step nine, testing and characterizing the injection molded ultra-high strength titanium alloy.
6. The preparation method according to claim 5, characterized in that: The titanium alloy powder raw material in step 1 has a D50 particle size of 7 to 15 μm and an oxygen content of less than 2280 ppm.
7. The preparation method according to claim 5, characterized in that: The binder in the mixture in step 2 is a wax-based binder including paraffin and / or a plastic-based binder including polyoxymethylene, and the titanium alloy powder raw material accounts for 56% to 70% of the total volume of the mixture. In step 3, the kneading temperature of the plastic-based binder system is 180-190°C, and the kneading time is 1-3h; the kneading temperature of the wax-based system is 155-165°C, and the kneading time is 1-3h; In step 4, the granulation temperature of the plastic-based binder system is 180°C, the granulation temperature of the wax-based binder system is 160°C, the extrusion speed is 10-20Hz, the feeding speed is 5-10Hz, the cutting speed is 5-10Hz, the particle size of the pellets is 3mm, and the particle length is 2-4mm.
8. The preparation method according to claim 7, characterized in that: The injection mold in step five is a stretch strip mold, and the injection parameters used for plastic-based feeding are injection temperature of 180-190°C, injection pressure of 180-195 bar, injection speed of 60-80%, and mold temperature of 50-65°C; the injection parameters used for wax-based feeding are 155-170°C, injection pressure of 180-195 bar, injection speed of 60-80%, and mold temperature of 40-60°C.
9. The preparation method according to claim 8, characterized in that: In step six, the degreasing method of the plastic-based tensile strip injection blank is oxalic acid degreasing, and its parameters are: degreasing temperature 120-150°C, and degreasing time 8-18h; the degreasing method of the wax-based tensile strip injection blank is solvent degreasing, and the solvent used is trichloroethylene, and the solvent degreasing parameters are: solvent temperature 30-60°C, and degreasing time 8-20h.
10. The preparation method according to claim 5, characterized in that: In step 7, sintering is carried out in a molybdenum sheet vacuum sintering furnace, the temperature is increased at a rate of 2 to 5°C / min, and thermal debinding is performed at 300°C, 450°C, and 550°C for 1 to 2 hours, respectively, and then the temperature is increased to 1000 to 1300°C at a rate of 2 to 10°C / min and maintained for 1 to 5 hours, and the furnace is cooled to room temperature; the thermal debinding atmosphere is high-purity argon gas, and the vacuum degree during vacuum pressureless sintering is 0.01Pa; In step eight, the heat treatment is a solution-aging heat treatment, the solution temperature is 800-1000°C, the heating rate is 5-15°C / min, the temperature is kept for 1-8h, and then the aging treatment is carried out after rapid cooling to room temperature; the aging temperature is 400-700°C, the heating rate is 5-15°C / min, the temperature is kept for 1-6h, and the temperature is rapidly cooled to room temperature.
Citation Information
Cited By
Titanium alloy and preparation method therefor, structural member, and terminal device
WO2026184443A1